(untitled) (Bangladesh Heart Journal, 2020)
Background: Diabetes mellitus (DM) is an established major cardiovascular risk factor associated with increased prevalence of coronary artery disease (CAD). Patients with diabetes often have numerous concomitant cardiac risk factors with a higher incidence of acute myocardial infarction (AMI) and congestive heart failure (CHF). Patients either with or without a prior history of DM may present with hyperglycemia during AMI. We analysed our population to determine whether admission hyperglycemia was a strong risk factor for in-hospital mortality and morbidity in patients with AMI and may be even stronger than a previous history of diabetes.In-hospital death risk of AMI patients without DM was about 2 to 4 times higher in patients with hyperglycemia than in those without hyperglycemia. Methods: This Prospective observational study was carried out at the National Institute of Cardiovascular Diseases (NICVD), Dhaka. A total number of 200 STsegment elevation AMI patients were enrolled in this study as per inclusion and exclusion criteria. They were subdivided on the basis of admission blood glucose into two groups. Group-1A and 2A were 50 patients with blood glucose <200mg/dl (<11.1mmol/l) and Group-1B and 2B were 50 patients with blood glucose ≥200mg/dl (11.1 ≥mmol/l). The numerical data obtained from the study were analyzed and significance of differences were estimated by using statistical methods. Computer based SPSS (Statistical Package for Social Science) were used. Results: In the present study mean age of the male and female were 56.10±11.86 and 57.83±13.74 years, p>0.05%. There was no significant difference regarding risk factors and smoking was higher in both group. Regarding inhospital adverse outcome, death was significantly higher in hyperglycemic non diabetic group (p<0.0001). It was two times (56%) higher than diabetic hyperglycemic (28%) group.Cardiogenic shock (66%) and CHF (56%) were also more common in hyperglycemic non diabetic group. Lowest patients (8%) died of AMI without DM with random blood glucose <11.1 mmol/l (controlled). On the other hand highest improvement was in the controlled group (p<0.0001).Multivariate analysis showed Diabetic status with normal blood sugar was a predictor of adverse outcome; but patients with hyperglycemia and no history of diabetes had a worse outcome and were independently associated with significant risk of in-hospital mortality. Age group >65 years and Male sex were also associated with significant in-hospital mortality. Conclusion: Independent of diabetic status, the occurrence of hyperglycemia during AMI is associated with a subpopulation of patients at particularly high risk for an adverse clinical outcome. Even with the highly efficacious treatment strategies currently available, persons presenting with AMI and hyperglycemia are at increased risk for cardiogenic shock and CHF or death in hospital. Bangladesh Heart Journal 2020; 35(1) : 14-19